DAMPAK PEMENUHAN MISI ORGANISASI DAN DUKUNGAN ORGANISASI YANG DIRASAKAN TERHADAP KINERJA PEGAWAI: KETERIKATAN KERJA SEBAGAI VARIABEL MEDIASI (STUDI KASUS PADA DINAS PERTANIAN DAN PRKEBUNAN ACEH) - Mutiara Septri Pertiwi; Nasir Azis; Mahdani Ibrahim (Jurnal Magister Manajemen, 2018)
The purpose of the study to determine the effect of organizational mission fulfillment and organizational support on job performance through work enggagement as a mediation variable. The study used primary data obtained by distributing questionnaires to 171 respondents, respondents are permanent employees at the Department of Agriculture and Plantation Aceh. Quantitative research method and data analysis using structural equation modeling with SPSS + AMOS program. The result of research indicates that the fulfillment factor of organizational mission that is built in the research model has an effect on work enggagement, organizational support factor has an effect on work enggagement, fulfillment factor of missions built in the research has no effect on job performance, organizational support factor influence to job performance, work enggagement on employee performance, organizational mission fulfillment factors proved not to have indirect relationship with job performance mediated by work enggagement, organizational support factor proved not to have indirect relationship with job performance mediated by work enggagement factor at Agriculture and Plantation Office of Aceh